Compaction Quality Fine Control of Fresh Concrete Based on Vibration Energy. Issue 1 (January 2021) - Ce, Bian; Ningbo, Li; Zhenghong, Tian; Feng, Zhu; Xingshun, Lei
Abstract: To solve the problem of difficulty in controlling the construction quality of fresh concrete due to the low applicability and accuracy for the existed referencing vibration time when using internal vibrator, an innovative parameter of vibration energy density is created based on concept of energy and a hardened porosity prediction model is constructed considering the parameter and mix characteristics. The model is used to obtain the minimum porosity value of concrete and corresponding energy density threshold under certain ratio conditions. Finally, the accuracy and effectiveness of method are verified by field tests. The results show the method can realize precise quantitative quality control of concrete vibration and guide the construction work.